2020
DOI: 10.3389/fvets.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Blood Groups in Domestic Cats in the Saskatoon and Calgary Areas of Saskatchewan and Alberta, Canada

Abstract: The purpose of this study was to evaluate blood types of domestic cats in two cities in Western Canada (Saskatoon, Saskatchewan and Calgary, Alberta), as well as to determine the risk of mismatched transfusion and neonatal isoerythrolysis. Several cat studies around the world have shown variability in the prevalence of blood types in domestic and pedigree cats. Canadian data based on feline blood types is based out of Montreal. In this study the cohort of cats revealed a higher than anticipated prevalence; of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…This epidemiological study confirmed the prevalence of type-A blood at a worldwide high level in both investigated areas of Northern (Lombardy) and Southern (Sicily) Italy compared to studies in non-pedigree cats in Europe [9,14,25,[41][42][43][44], America [8,10,23,29,37,45] Australia [27,28] and Asia [13,22,[46][47][48]. Although the prevalence of type-A cats in Southern Italy was significantly lower than in Northern Italy, blood type-A is more prevalent in southern cats as has previously been reported in non-pedigree cats from Northern and Central Italy [12,[32][33][34], in Ragdolls in Northern Italy [38] and in Maine Coons in Central Italy [35].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This epidemiological study confirmed the prevalence of type-A blood at a worldwide high level in both investigated areas of Northern (Lombardy) and Southern (Sicily) Italy compared to studies in non-pedigree cats in Europe [9,14,25,[41][42][43][44], America [8,10,23,29,37,45] Australia [27,28] and Asia [13,22,[46][47][48]. Although the prevalence of type-A cats in Southern Italy was significantly lower than in Northern Italy, blood type-A is more prevalent in southern cats as has previously been reported in non-pedigree cats from Northern and Central Italy [12,[32][33][34], in Ragdolls in Northern Italy [38] and in Maine Coons in Central Italy [35].…”
Section: Discussionsupporting
confidence: 79%
“…However, no type-AB cats were found in early studies in Central Italy [26,33]. Type-AB blood is rare (≤1%) in non-pedigree cats in most studies [8,10,11,14,16,27,29,37,38,[41][42][43]47,48,50,51]. The prevalence of type-AB blood in non-pedigree cats in Southern Italy was therefore very high and comparable only with that reported in non-pedigree cat populations from Japan (9.7%) and Israel (14.5%) [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should consider the effect of blood type on outcome in large animal xenotransfusion. Cats have 3 main blood groups ( 31 , 32 ), and over 13 blood groups have been described for dogs ( 33 ). Erroneous blood typing in 2 cats recently led to non-fatal acute hemolytic reactions following xenotransfusion with canine blood ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, type A blood type is the most common, type B is less common, and type AB is rare, with a global frequency lower than 1%. These frequencies vary geographically between and within countries, with type A being the most common blood type in non-pedigree cat populations in different countries, as reported by several studies worldwide [ 2 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Variations are also described among breeds, with type B showing a high frequency in some pure breeds [ 21 , 48 , 49 , 50 ].…”
Section: Ab Blood System In Domestic Catsmentioning
confidence: 91%